Measuring disparities in non-school costs and revenue capacity among Massachusetts cities and towns - Katharine Bradbury; Bo Zhao (Federal Reserve Bank of Boston, 2007)
This paper develops new measures of environmental costs and local revenue capacity as the basis for a new municipal aid formula in Massachusetts. On the cost side, unlike previous studies, we quantify the effects on local non-school spending of characteristics related to uncontrollable costs. On the capacity side, we account for the constraints of a tax limitation, for the first time in the literature, by estimating these constraints as a function of residents' incomes. The estimates of costs and capacity indicate substantial inter-local fiscal disparities in Massachusetts. Our approach is potentially applicable to other states.
Keywords: H70; H71; H72; H73; H77; H83; H20; 330; Fiscal disparities; municipal costs; revenue capacity; property tax; state aid; tax limitation